2008
DOI: 10.1590/s0036-36342008000300009
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tuberculosis treatment defaulting: an analysis of perceptions and interactions in Chiapas, Mexico

Abstract: Objective. To analyze the perceptions and interactions of the actors involved in anti-tuberculosis treatment, and to explore their influence in treatment defaulting in Los Altos region of Chiapas, Mexico. Material and Methods. From November 2002 to August 2003, in-depth interviews were administered to patients with PTB, patients' family members, institutional physicians, community health coordinators, and traditional medicine practitioners. Results. We found different perceptions about PTB between patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Additionally, we found that the sensitivity of the smear testing was slightly lower than 50% in the primary care centers and in communities, and that the proportion of patients with active PTB that was receiving treatment was only 50% in the primary care centers, and 10.5% in the studied communities [10]. Also, we found high rates of anti-TB treatment defaulting [11], and very high levels of PTB multidrug-resistance (MDR): 4.6% and 29.2% primary and secondary MDR-TB, respectively. In fact, 14% of all studied PTB patients had MDR.…”
Section: Several Studies Have Been Carried Out By Our Team In Areas Omentioning
confidence: 72%
See 1 more Smart Citation
“…Additionally, we found that the sensitivity of the smear testing was slightly lower than 50% in the primary care centers and in communities, and that the proportion of patients with active PTB that was receiving treatment was only 50% in the primary care centers, and 10.5% in the studied communities [10]. Also, we found high rates of anti-TB treatment defaulting [11], and very high levels of PTB multidrug-resistance (MDR): 4.6% and 29.2% primary and secondary MDR-TB, respectively. In fact, 14% of all studied PTB patients had MDR.…”
Section: Several Studies Have Been Carried Out By Our Team In Areas Omentioning
confidence: 72%
“…It is therefore necessary to reduce the cultural and socioeconomic barriers between health care providers and people [10]. Not surprisingly, some results of our investigations show that apart from cultural barriers, there are also structural barriers [11].…”
Section: Tuberculosis -Current Issues In Diagnosis and Management 452mentioning
confidence: 73%
“…The women's health is affected by structural problems in the health system, for example, they not participate at all in planning of health services and the high levels of poverty in the majority of them in rural and indigenous areas, constitutes a serious obstacle to enjoyment their rights [9] Mexico's Constitution prohibits discrimination in the enjoyment of all rights, including the right to health protection, and recognizes that every person in the country shall enjoy the guarantees granted by this Constitution, and that "men and women are equal before the law", but in practice, in Chiapas it is not occurring. People with TB often are discriminated with exclusion and rejection, by both society and health personnel [10,15,17,19,20,31], mainly because they are considered as source of infection [10,23]. Health personnel avoid contact with patient with consequences in adequate timely diagnosis, treatment and follow up, and even refusal to provide health care [43].…”
Section: Principle Of Non-discriminationmentioning
confidence: 99%
“…Although DOTS has been the landmark of TB control, many people with TB remain undiagnosed or are diagnosed only after long delays. This strategy was developed only from a biomedical orientation without including other dimensions such as social, economic, cultural, linguistic and physical access to TB services as well as migration and stigmatization [10,17,19,21,23,26].…”
Section: Right To Receive Free Timely and Appropriate Diagnosis And mentioning
confidence: 99%
See 1 more Smart Citation